PERANCANGAN IDENTITAS VISUAL UNTUK PERTANIAN MODERN ”GUMINEPONIK” DAN IMPLEMENTASINYA - I Wayan Adi Putra Yasa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2021)
Gumineponik is one of the UMKM engaged in the hydroponic business. Besides offering hydroponic installations, hydroponic equipment, and plant nutrition, it also offers innovative processed products such as vegetable fruit juices and fruit and vegetable spring rolls. In introducing its business and products, gumineponik requires a visual identity in the form of a logo that will be implemented in promotional media. Data were collected naturally and presented in a qualitative descriptive form. Data collection was carried out using interviews and direct observation. In addition, it is supported by theoretical studies and documentation. Logo design starts from brief design, research and brainstorming, alternative designs, presentations and revisions in the process of getting the selected logo for gumineponik. The chosen logo is a combination of the letter G and leaves as a symbol of agriculture. The selected logo is then implemented on the packaging of juice and spring roll products. In addition, it is also implemented on business cards, pricelist and x-banner media as supporting media.